2020
DOI: 10.1016/j.neuroimage.2020.117096
|View full text |Cite
|
Sign up to set email alerts
|

Functional engagement of white matter in resting-state brain networks

Abstract: The topological characteristics of functional networks, derived from measurements of resting-state connectivity in gray matter (GM), are associated with individual cognitive abilities or specific dysfunctions. However, blood oxygen level-dependent (BOLD) signals in white matter (WM) are usually ignored or even regressed out as nuisance factors in the data analyses that underlie network models. Recent studies have demonstrated reliable detection of WM BOLD signals and imply these reflect associated neural activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 52 publications
(57 reference statements)
3
30
0
Order By: Relevance
“…Functional connectivity measures were computed between seed areas for ROI-to-ROI analysis and to identify patterns of ROI-to-ROI connectivity. Partial correlation was used to estimate the functional connectivity between two nodes (Li et al, 2020). We compared functional connectivity between the RW and TSD scans using two-tailed paired t-tests.…”
Section: Functional Connectivity Analysismentioning
confidence: 99%
“…Functional connectivity measures were computed between seed areas for ROI-to-ROI analysis and to identify patterns of ROI-to-ROI connectivity. Partial correlation was used to estimate the functional connectivity between two nodes (Li et al, 2020). We compared functional connectivity between the RW and TSD scans using two-tailed paired t-tests.…”
Section: Functional Connectivity Analysismentioning
confidence: 99%
“…In practice, the average BOLD fluctuations within WM have often been regressed out as a nuisance covariate 5,6 . In recent years, a growing body of literature has recognized that changes in BOLD signals in WM may reflect neural activities [7][8][9] and, by using appropriate methods, BOLD changes associated with external stimuli can be reliably detected with conventional fMRI [10][11][12][13][14][15] . However, the sensitivity of detecting WM activation is often much lower compared to GM, possibly due to incorrect assumptions made about the time courses of responses that are incorporated into regression models for detection 16 .…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, Mishra et al (2020) showed that varying experimental task parameters results in a coupled modulation of the BOLD signal in the visual cortex and relevant WM tracts, corroborating past findings of simultaneous BOLD activations in structurally-connected regions of GM and WM (Mazerolle et al, 2010). Furthermore, a growing number of recent studies have shown that low frequency BOLD fluctuations can be used to estimate the dynamic functioning of fiber tracts (Gore et al, 2019), in both health (Marussich et al, 2017; Huang et al, 2018b; Li et al, 2020b) and disease (Jiang et al,2019; Ji et al, 2019; Gao et al, 2020), providing a powerful means to study how information is transferred and integrated between functionally specialized cortices.…”
Section: Introductionmentioning
confidence: 99%